Didáctica de la geografía y su aplicación a la enseñanza de la geografía en el tercer ciclo y la enseñanza diversificada de Costa Rica - Vargas Ulate, Gilbert (2009)
The Didactics of Geography in the schools must leave traditional and obsolete elements that constitute the basis of the geographic knowledge at the present time. On the matter, the education of that discipline is in a deficient and limited situation in Costa Rica for two reasons: geographic formation of the teaching staff is limited, partial and traditional, and the absence of reflection on the Didactics of the discipline. In the article, it is maintained the thesis that the students must acquire slight knowledge and abilities that interrelate, but so that it happens, it is necessary to structure the education of Geography gradually and significantly for the students.